Faktor yang Memengaruhi Niat Adopsi Teknologi Fertigasi pada kelompok Tani Guyub Rukun Kabupaten Sleman DI Yogyakarta - Rico Rayhan; Epsi Euriga; Adinugra Rimartin (Jurnal Greenation Pertanian dan Perkebunan, 2026)
Significant fluctuations in cayenne pepper productivity in Sleman demand the adoption of precision agricultural technology, but the low active participation of farmer group members is a crucial obstacle in the modernization process. This study aims to analyze adoption intentions and examine the influence of performance expectations, business expectations, social influence, supporting conditions, and participation on the adoption intentions of fertigation technology in the Guyub Rukun Farmer Group. Quantitative methods were used with a sample of 35 respondents, analyzed using multiple linear regression. The results showed that farmer participation was dominated by passive participation. Simultaneously, all five variables significantly influenced adoption intentions (F 4.128); (p 0.006) with an Adjusted R Square of 31.5%. Partially at the 10% alpha level, only performance expectations (p 0.058) and social influence (p 0.054) had a significant positive effect, while business expectations, supporting conditions, and participation did not have a significant effect. Increasing the intention to adopt fertigation requires concrete proof of economic-technical benefits and optimization of the role of key figures (opinion leaders) to encourage group members who tend to be passive.